PERAN KEPALA DESA DALAM PROSES PENYELESAIAN SENGKETA LAHAN (STUDI KASUS SENGKETA LAHAN ANTARA MASYARAKAT DESA DUSUN TUA DENGAN PT. SARI LEMBAH SUBUR DESA DUSUN TUA KECAMATAN PANGKALAN LESUNG KABUPATEN PELALAWAN)2020 - Rido Alhafizh; Adlin ' (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2023)
So important is land for human life on earth, it is not uncommon for land rights to be fought over. Today there are frequent land disputes within the community, both disputes between individuals and individuals, as well as between individuals and community groups, also between communities and companies, and between communities and the government. This happened in Dusun Tua Village, Pangkalan Lesung District, Pelalawan Regency where a dispute occurred between the community who were members of the Dusun Tua Sejahtera Cooperative and PT. Subur Valley Sari. This study aims to determine the role of the village head in the process of resolving land disputes between the people of Dusun Tua Village and PT. Subur Valley Sari. The method in this study uses a descriptive research type using a qualitative approach. Sources of data consist of primary data and secondary data collected through interviews and documentation. Data analysis used qualitative data analysis techniques with interactive models. The results of this study indicate that the village head plays a role in resolving disputes that occur between the community and the company. Where in his leadership the village head as the village leader mediated this problem and resolved it peacefully. Starting from receiving complaints and consulting the community, negotiating with disputing parties and conducting mediation which resulted in an agreement that the community paid off the remaining debt to PT. Sari Lembah Subur by borrowing money from the bank by pawning 5 billion land certificates and the rest by dividing the palm oil yields by 30% and 70% with the company. Keywords: Village Head Leadership, Dispute Resolution